A MEASURE OF CUSTOMER SATISFACTION WITH MRF TYRES - Dr. G. SATHIYAMOORTHY; RAJA, ROXIA (Universitas Nahdlatul Ulama Surabaya, 2024)
The behavior of customers toward MRF Tyre, particularly in Tirupur city, is the subject of this survey. The purpose of the study was to examine customer satisfaction with MRF tyre, to determine which media outlets encourage consumers to purchase MRF tyre and to ascertain the degree of satisfaction with various MRF tyre components. One source of primary data is a questionnaire. In Tirupur city, a survey was conducted, and 120 people responded. Secondary data for the study was gathered from relevant journals and websites. For this study, non-probability sampling strategies were employed. The statistical tools employed were one-way ANOVA and simple percentage analyses. Developed a hypothesis and tested it using the reliability and normality tests. Results of the analysis showed that most respondents were influenced by friends and that they were generally happy with the different aspects of MRF Tyre. In conclusion, the majority of Tirupur city residents who use MRF tyre for their vehicles felt that the tyre were both comfortable and reasonably priced.